A Survey of Islamic Banking Products Knowledge in Villages: Evidence from Talang Bakung Village - Erwin Saputra Siregar; Welly Puspita Sari; Arsa Arsa (Faculty of Economics UIN Maulana Malik Ibrahim Malang, 2021)
This research aims to determine the Level of Public Knowledge of Islamic Banking Products. The problems discussed are public knowledge of Islamic banking products and what factors determine the level of public knowledge of Islamic banking products in Talang Bakung Village. The sample is 99 respondents. The sampling method is Purposive Sampling, the sampling technique based on the criteria, namely age and religion. Data were collected by interviewing and filling out questionnaires addressed to the people of Talang Bakung sub-district in Jambi city. The research results show that the people's knowledge of Talang Bakung Village regarding Islamic banking products is deficient. Some people already know about Islamic banks but do not know about the products. The factors that determine the level of knowledge of the Talang Bakung sub-district are education, employment, age, experience, and environmental factors.